Multifaceted roles of Candida albicans and Streptococcus mutans in contributing to polybiofilm infections in early childhood caries - Anto Benignus Francis; Rajendra Prasad Settem; Moghanram Jeyamoorthy; Venkata Harshith Nuthangi; Ashu Sharma; Satish Kumar Rajasekharan (Frontiers in Cellular and Infection Microbiology, 2025)
This succinct article addresses the multifaceted interactions between the fungal organism Candida albicans and the Gram-positive bacterium Streptococcus mutans in the development of oral biofilms and pathobiology of oral diseases. S. mutans is considered to be a major pathogen in the development of dental caries. It is often found to interact with C. albicans in oral infection settings. The interaction of these organisms is often mediated via the binding of Glucosyltransferase (GtfB) enzyme secreted by S. mutans to C. albicans surface proteins Als1 and Hwp1. During these interactions, both C. albicans and S. mutans exhibit increased gene regulatory activity, leading to the modulation of virulence attributes and adaptation to environmental changes. This results in the strong attachment of the species to tooth surfaces and increased resistance of the mixed species biofilms to external factors. Mechanistically, intercellular communication between these species in mixed biofilms through quorum sensing and production of exoenzymes such as glucosyltransferases account for the synergy and modulation of their virulence attributes. Specifically, these mixed-species biofilms exhibit increased acid production and enhanced resistance to antimicrobial agents. Understanding these complex interkingdom pattern of interactions is essential to develop efficient therapeutic approaches against biofilm-associated oral infections. The review also highlights probiotic strategies to interfere with these interkingdom interactions to combat oral diseases like early childhood caries (ECC).